Duration of nivolumab for pretreated, advanced non–small‐cell lung cancer. (15th May 2020) - Geier, Margaux; Descourt, Renaud; Corre, Romain; Léveiller, Guillaume; Lamy, Régine; Goarant, Éric; Bizec, Jean‐Louis; Bernier, Cyril; Quéré, Gilles; Amrane, Karim; Gaye, Elisabeth; Lucia, François; et al.
Abstract: Background: A standard of care for pretreated, advanced non–small‐cell lung cancers (NSCLCs), nivolumab has demonstrated long‐term benefit when administered for 2 years. We aimed to better discern an optimized administration duration by retrospectively analyzing real‐life long‐term efficacy in a prospective cohort. Methods: All nivolumab‐treated adults with advanced NSCLCs (01/09/2015 to 30/09/2016) from nine French centers were eligible. On 31/12/2018, patients who are alive ≥ 2 years after starting nivolumab were defined as long‐term survivors (LTSs) and were divided into three nivolumab treatment groups: <2, 2, or > 2 years. Co‐primary endpoints were LTSs' progression‐free survival (PFS) and overall survival (OS). Results: The median follow‐up was 32 months (95% CI, 31.0 to 34.0). The 3‐year OS rate for the 259 cohort patients was 16.6%. Among them, 65 were LTSs: 47 treated < 2 years, 7 for 2 years, and 11 > 2 years. Their respective characteristics were: median age: 59, 52, and 58 years; smoking history: 92.9, 100, and 100%; adenocarcinomas: 66, 57.1, and 54.5%. LTSs' median (m)PFS was 28.4 months; mOS was not reached. LTSs' objective response rate was 61.6%. mOS was 32.7 months for those treated < 2 years and not reached for the others. The > 2‐year group's 3‐year OS was longer. Twenty‐eight LTSs experienced no disease progression; 7 had durable complete responses. However, LTSs had more frequent and more severe adverse events. Conclusion: In real‐life, prolonged nivolumab use provided long‐term benefit with 16.6% 3‐year OS and 25% LTSs. Survival tended to be prolonged with nivolumab continued beyond 2 years. Prospective randomized trials with adequate design are needed. Abstract : Phase III trials didn't provide an optimal duration of immunotherapy for responder or stable patients in advanced non‐small‐cell lung cancer. A 2 years‐fixed duration or long‐term therapy are proposed to clinicians. The results of this observational study of 65 long‐term survivor pretreated patients showed a trends toward improvement of survival outcomes when continuing nivolumab after two years.